Digital Health Interventions to Improve Parental Literacy and Nutritional Status of Preschool-Aged Children: A Systematic Review - Ropitasari Ropitasari; Fanny Kartika Fajriyani; Oktia Woro Kasmini Handayani; Nahdiyah Karimah; Herliana Riska (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: Nutrition of preschool children, especially toddlers, greatly determines the quality of life of children in the future. In line with the rapid development of information technology in the digital era, many health promotion media have been developed to improve the digital literacy of parents. Assessment of children's nutritional status by utilizing technology is considered more accurate and easily accessible to parents. This study aims to conduct a systematic review related to digital health interventions as an effort to improve parental literacy and nutritional status of children under five. Subjects and Method: This study is a systematic review using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach. Articles were obtained from Scopus, PubMed, ScienceDirect, Web of Science, and Google Scholar databases for the period 2020-2025. Inclusion criteria include English-language studies, quantitative, qualitative, and mixed-methods research, full text, evaluating digital tools, AI-based models, or behavioral-based approaches to improve the nutritional status and eating behavior of toddlers. The assessment of the quality of the study uses Critical Appraisal Skills Programs (CASP) for quantitative and qualitative research. Results: 7 articles were found consisting of 2 articles from China and Sweden, 1 article each from Indonesia, Thailand, Nigeria. The use of digital technology has developed in various countries with a focus on improving parents' digital literacy, especially related to children's health, including anthropometric measurements, assessment of children's nutritional status, and dietary recommendations based on the results of nutritional status analysis. Conclusion: Digital health intervention innovations are considered effective in improving parental literacy and nutritional status of children under five